PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN - Gita Vanya Meisara; Hotman Napitupulu (Jurnal Manajemen Bisnis Krisnadwipayana, 2019)
This research is intended to examine the effect of price and product quality on customer satisfaction both partially and simultaneously at PT Sophie Paris Indonesia, Pondok Gede branch. The research method used is descriptive and verification research methods. Data was collected using the questionnaire method, and data analysis used was multiple linear regression analysis.The results showed that price, product quality and customer satisfaction.